The influence of auditor ethics and auditor experience on audit quality - Rosana Setyaningrum; Retno Murnisari (Institute of Computer Science (IOCS), 2026)
The goal of this study is to examine the simultaneous effects of accountants' professional ethics, including professional responsibility, integrity, and objectivity, as well as the auditors' experience with regard to audit quality. The research specimen was obtained through purposive sampling from two public accounting firms in Surabaya, there were 30 responses in total. This analysis utilized multiple linear regression, assisted by IBM SPSS Statistics 26 and Microsoft Excel. It is concluded that the auditors' ethics have a significant and positive influence on audit quality, while their experience also has varying degrees of significance in enhancing auditors’ technical and analytical capabilities. Simultaneously, both variables make a strong contribution to improving the quality of audit. The implications from this research suggest that adhering to strong ethical standards in the profession, along with adequate auditor experience, can enhance public and stakeholders confidence have in the reliability of audited financial reports